Effectiveness Of Achieving Speech Text Writing Skills with The Circ and Ttw Models Based on Students' Reading Abilities - Fatqurrahman Anugrah Utomo; Subyantoro Subyantoro; Rahayu Pristiwati (Universitas Negeri Semarang, 2025)
Of the many writings skills learning, theoretically the most important role in growing and developing the potential of each individual student in an effort to express ideas and concepts in good and correct Indonesian is writing a speech text. So, the right learning model is needed. Thus, there is a purpose of this study, namely, to prove the level of effectiveness of learning to write a speech text using the Cooperative Integrated Reading and Composition model and the Think Talk Write model based on the reading comprehension skills of grade VIII junior high school students. In this study, quantitative research was applied in the form of quasi-experimental design research with the Non-equivalent Pretest-postest Design model. The results of this study state that the Cooperative Integrated Reading and Composition model is more effective to be applied than the Think Talk Write model in learning persuasive speech text writing skills. This can be proven from the results of the Independent Sample T-Test which states a sig value of 0.042. So, it can be interpreted that sig 0.042 <0.05 or a significance value of 0.042 is less than 0.05. So, in accordance with the research basis which states that the Cooperative Integrated Reading and Composition model has a very big influence on students' reading ability which will then have a significant impact on writing skills, in this case the skill of writing speech texts. Meanwhile, the Think Talk Write model does not have a significant influence on students' writing ability because it does not pay attention to students' reading ability levels. The suggestions addressed in this study to teachers, schools, and further research.